Application of a Boltzmann machine to timetable design - Piwakowski, Konrad; Trojanowicz, Marek (Zielona Góra: Uniwersytet Zielonogórski)
This paper contains a description of the construction of a Boltzmann machine that can be applied to obtain a class-teacher timetable. In particular, this approach concerns requirements that are characteristic to primary and secondary schools. The conditions of asymptotic convergence to an optimal solution are presented.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka